"A Big Circle of Unity": Incarcerated Fathers Being-in-Text. (September 2016) - Muth, William
This study explores the lived experiences of incarcerated fathers "being-in-text" with their children. It draws on Husserlian and Heideggerian notions of intentionality that are partly deconstructed by Derrida and further "posted" by Vagle's notion of post-intentionality and Barad's posthumanism. Of particular interest is a week-long prison-based mural project—framed in terms of multimodal, existential, identity work—that provided material support for fathers' ontological shifts from being prisoners to being fathers in phenomenal time and space. The study revealed that being-in-text was lived as a contingent and suspenseful "being-in" time and space, oriented in a "being for" children, even as other forces of being-in-prison discouraged fathers from looking up toward horizons beyond prison walls. These dehumanizing forces of prison were a form of blind loyalty—a looking down and away from life outside prison and narratives of belonging. The study further revealed a possibility for becoming fathers as prisoners looked up into the eyes of (present and imagined) family members. Literacy events provide contexts for prisoners to be answerable to their children. But being-in-text and being-in-prison are lived as a singular and constant tension of "staging" that raises ethical concerns about the risks and costs of these ontological shifts. From this, an appeal is made for a nuanced valuing of prisoners as subjects rather than objects, and for further exploring a "posted" phenomenology's role in literacy research and social justice work.